THEOLOGIZING IN INDIA An Exploratory Method - Manickam, Thomas (Journal of Dharma, 1980)
The Seers call that which is One in many ways" (Rv. I : 164,46). Let me draw my inspiration for this exploratory approach to theologizing in India from the above-quoted basic insight of the Vedic Seer. Theology, as I understand it, is man’s language (Logia) about God. It is his expression of his experience of God in whom he believes and looks up to for some sort ·of ultimate meaning for his life. A language is meant for communicating one’s inner experience, theology is primarily concerned with man’s communication of his God-experience. Hence God as God is the primary subject-matter of its communication. So in this exploration I would like to confine my inquiry to that aspect of man’s God-experience in India without immediately attempting at creating Indian parallels for the traditionally known branches of Christian" Systematic Theology", such as Christology, Pneumatology, Ecclesiology or whatever else is relevant to Indian context .